STATE OF THE HORMONAL PROFILE IN ENDOMETRIAL HYPERPLASIA - Kachailo, I.A.; Guz, I.A.; Kuzmina O.О. (World of Medicine and Biology, 2023)
The research data of 93 patients were analyzed. Patients were divided into three clinical groups depending on the form of endometrial hyperplasia: group 1: with uncomplicated non-atypical endometrial hyperplasia – 53 patients; group 2: with complex non-atypical endometrial hyperplasia – 22 patients; group 3: with simple atypical endometrial hyperplasia – 18 patients. The control group consisted of 20 healthy women. Comparative analysis showed that the level of hormones in the 1st phase of the menstrual cycle was not significantly different between the groups for most indices of luteinizing hormone in group 2 compared to groups 1 and 3 (p < 0.01). The study of hormonal status in women of 3 clinical groups showed that, compared to the control group, there was a significantly greater increase in the level of testosterone in blood plasma (p < 0.05). Progesterone content in the control group was lower (almost by 5 times) than the control level (p < 0.001). The estradiol level in groups 1 and 2 decreased and was three times lower compared to the control group (p < 0.001). With simple atypical EH, the concentration of estradiol was sharply increased compared to the control groups, 1 and 2, which confirms the stimulation of the proliferative processes’ development in the endometrium.